Colonial debts : the case of Puerto Rico - Zambrana, Rocío (Radical Américas., 2021)
"Rocío Zambrana uses the current political-economic moment in Puerto Rico to outline how debt functions as both an apparatus that strengthens neoliberalism and the island's colonial relation to the United States."--